Multitone modulation and demodulation for channels with SNR uncertainty - Baum, C.W.; Conner, K.F. (Proceedings 1995 IEEE International Symposium on Information Theory, 1995)
A multitone transmission scheme that uses a nonlinear binary code to specify multitone signal constellations is proposed and motivated. A technique for designing the nonlinear code is presented, and methods for making symbol decisions and erasures without knowledge of signal and noise strength parameters are given. The performance of a system using this scheme with Reed-Solomon error control coding is discussed. Additionally, we show that incorporation of errors-and-erasures decoding provides significant performance improvements in channels subject to AWGN and Rayleigh fading.